Lintas Budaya: Peranan dan Pemahaman dalam Aktivitas Bisnis Internasional - Budiarsi, Sri Yunan (Jurnal Widya Manajemen & Akuntansi, 2003)
To survive in today's global market place, firms must be able to quickly exploit opportunities presented them anywhere in the world and respond to changes in domestic and foreign markets as they arise.The firms will deal with multiple government, multiple political systems, and a variety of languages and cultures in different parts of the world. Globalization ha,e raised the frequency of cross-cultural contacts and increased the importance of a firm's understanding the role of culture in business activities if it wants to remain competitive internationally. This article will give you a view, of how cross cultural understanding in International Businesses. The basic elements of culture are social structure, language, communication, religion, and values and attitudes.